The effect of anxiety on the parameters of carpal tapping in patients with post-stroke epilepsy - E. A. Narodova; N. A. Shnayder; V. V. Narodova; E. E. Erahtin; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния)
Aim. To study the characteristics of carpal tapping in the normal condition and the effect of subclinical anxiety on its parameters with post-stroke epilepsy in adults.Material and methods. We examined 140 people aged from 22 to 55 years. The total sample was divided into 3 observation groups: the first (I) group included healthy volunteers; the second (II) group included the patients with post-stroke frontal lobe epilepsy; the third (III) group included the patients with post-stroke temporal lobe epilepsy. Each group was divided into two subgroups: subgroup Ia (33 people) included healthy volunteers who did not show reliably expressed symptoms of anxiety; subgroup Ib (27 people) included healthy volunteers with subclinical anxiety; subgroup IIa (20 people) included patients with post-stroke frontal lobe epilepsy who did not show reliably expressed symptoms of anxiety; subgroup IIb (20 people) included patients with post-stroke frontal lobe epilepsy with subclinical anxiety; subgroup IIIa (19 people) included patients with post-stroke temporal lobe epilepsy who did not show reliably expressed symptoms of anxiety; subgroup IIIb (21 people) included patients with post-stroke temporal lobe epilepsy with subclinical anxiety. The parameters of carpal tapping were investigated using the modified author’s program “Method of influencing an individual human rhythm through exogenous rhythmic stimulation”.Results. An acceleration of the individual rhythm was found in the presence of subclinically expressed anxiety both in healthy volunteers (from 1.13 Hz to 1.53 Hz) and in patients with post-stroke frontal lobe and temporal lobe epilepsy (from 2.07 Hz to 3, 45 Hz and from 1.83 Hz to 2.82 Hz, respectively). The rate of acceleration of the individual rhythm in patients with post-stroke frontal lobe and temporal lobe epilepsies was higher than in healthy volunteers (1.66 and 1.54 versus 1.35, respectively).Conclusion. The effect of anxiety on the parameters of carpal tapping was greater in patients with post-stroke epilepsy compared with healthy volunteers.